Thailand Financial Sector Assessment - International Monetary Fund (World Bank, Washington, DC, 2019)
A joint IMF-World Bank mission visited Thailand from November 1 to 16, 2018, and February 6 to 22, 2019, to update the findings of the Financial Sector Assessment Program (FSAP) conducted in 2008. This report summarizes the main findings of the mission, identifies key financial sector vulnerabilities, and provides policy recommendations.